2019
DOI: 10.1186/s12934-019-1133-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel surface display platforms for anchoring heterologous proteins in Saccharomyces cerevisiae

Abstract: Background Cell surface display of recombinant proteins has become a powerful tool for biotechnology and biomedical applications. As a model eukaryotic microorganism, Saccharomyces cerevisiae is an ideal candidate for surface display of heterologous proteins. However, the frequently used commercial yeast surface display system, the a-agglutinin anchor system, often results in low display efficiency. Results We initially reconstructed the a-agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…2019). Yang et al (2019) reconstructed the a‐agglutinin system by replacing two anchor proteins with one anchor protein and found that by directly fusing the target protein to the N‐terminus of the Aga1 protein and inserting a flexible linker, the display efficiency almost doubled. Mathew et al (2018) anchored HIV envelope protein Env to the yeast cell wall in which Env was either attached directly to the yeast cell wall α‐agglutinin as a C‐terminal fusion or fused to the secreted protein Aga2p either as an N‐ or C‐ terminal fusion, and found fusion of Aga2p at the C‐terminal provided higher expression levels by flow cytometry (Mathew et al .…”
Section: Probiotics Surface Display Systemmentioning
confidence: 99%
“…2019). Yang et al (2019) reconstructed the a‐agglutinin system by replacing two anchor proteins with one anchor protein and found that by directly fusing the target protein to the N‐terminus of the Aga1 protein and inserting a flexible linker, the display efficiency almost doubled. Mathew et al (2018) anchored HIV envelope protein Env to the yeast cell wall in which Env was either attached directly to the yeast cell wall α‐agglutinin as a C‐terminal fusion or fused to the secreted protein Aga2p either as an N‐ or C‐ terminal fusion, and found fusion of Aga2p at the C‐terminal provided higher expression levels by flow cytometry (Mathew et al .…”
Section: Probiotics Surface Display Systemmentioning
confidence: 99%
“…In yeast, typically, this comprises a cell wall protein (CWP) linked to glycosylphosphatidylinositol (GPI) ( Tanaka and Kondo, 2015 ; Lim et al, 2017 ). This platform combines fine-tuned gene expression and protein immobilization, which simplifies the purification process and allows the reuse and recovery of biocatalysts ( Yuzbasheva et al, 2011 ; Liu et al, 2014 ; Yang et al, 2019 ).…”
Section: Overview Of Yeast Surface Displaymentioning
confidence: 99%
“…This approach was used for surface display of Trypanosoma cruzi trans-sialidase [25], Aspergillus niger lipase ANL [26], mammalian membrane protein CD47 [27], and a number of mammalian antibodies and receptors [29,49,50]. Yang et al [51] constructed α-galactosidase fusion to the N-terminus of Aga1 with a flexible linker of 17 amino acids (composed of Ser and Gly) inserted between Aga1 part and α-galactosidase, and accomplished almost doubled display efficiency and 39% activity incensement in comparison to construct in which α-galactosidase was fused to the N-terminus of Aga1 without the linker. Tang et al [52] used an Aga1 and Aga2 protein pair display system for the construction of synthetic cellulosomes.…”
Section: Recombinant Protein Fusion To Other Gpi-anchored Proteinsmentioning
confidence: 99%
“…Using the Sed1 promoter was also favorable because efficient heterologous protein display was achieved by growth fa or prolonged period without any changes in the carbon source. Yang et al [51] constructed and compared fusions of α-galactosidase with serine-and threonine-rich regions and the GPI binding domains of Sed1, Cwp2, Dan4, Tos6, Srp2, and Pry3. Among them, Dan4 and Sed1 showed the highest display efficiency, but display efficiency and enzyme activities were not entirely dependable.…”
Section: Recombinant Protein Fusion To Other Gpi-anchored Proteinsmentioning
confidence: 99%